Membrane surface modification via ultraviolet-photografting for forward osmosis - Ahmad Fikri Hadi, Abdul Rahman (2019)
The shortage of freshwater has become a severe problem globally. To mitigate this problem, various technologies to cater the demand have been actively explored worldwide. An effective approach to address these water-related issues is via membrane technology. Specifically, the forward osmosis (FO) membrane, it has emerged as promising technology that has attracted much attention especially on the development of new FO membrane. Unfortunately, the commercial asymmetric cellulose triacetate membrane which is built with a low structural parameter and demonstrated decent FO performance suffers from high reverse salt diffusion (RSD) and show poor inhibition to biological attachment and hydrolysis. Thus, this study aims to modify commercial pressure-driven membrane using the surface modification technique for potential FO application. Among different successful membrane surface modification techniques, ultraviolet (UV) photografting is of particular interest, which offers a versatile means for providing the existing polymer with new surface functionalities, without affecting the bulk properties of the substrate. In this study, commercial ultrafiltration polyethersulfone (UFPES) and nanofiltration polyethersulfone (NFPES) membranes were modified via UV-photografting technique for FO application. The membranes were prepared under different acrylic acid monomer concentration (5, 15, 30 and 50 g/L) and grafting time (1,3 and 5 minutes). The membrane intrinsic properties were measured in reverse osmosis mode for water flux (Jw) water permeability (A), salt rejection (R), solute permeability (B) and in FO mode for water flux (Jv), structural parameter (S), and reverse salt diffusion (RSD). Membrane characterization was performed to evaluate the surface chemistry, functional group, surface roughness, surface morphology and hydrophilicity using the attenuated total reflection-Fourier transform infrared spectroscopy, x-ray photoelectron spectroscopy, atomic force microscope, field emission scanning electron microscopy and contact angle, respectively. The surface modification via UV-photografting has the potential in the FO application as incorporation of the carboxyl group enhanced the water flux as well as comparative RSD value. However, the experimental work reveals that UFPES membrane was not suitable for FO application compared to NFPES membrane. Unmodified UFPES was tested at a pressure of 3 bars exhibited salt rejection with R value of 0.39 % only when using the 200 ppm of sodium chloride (NaCl). Moreover, modified UFPES membrane also has R values which ranges below than 1 %. Thus, UFPES membrane has been excluded from the theoretical modelling and optimization processes. Mathematical modelling was performed on NFPES membrane to predict the water flux at different osmotic pressure as well as to suggest the range for the optimization processes. The obtained optimum conditions were 2.81 min grafting time and 27.85 g/L acrylic acid monomer concentration. Under these conditions, a maximum water flux of 1.52 ± 0.04 L.m-2.hr-1 was achieved with RSD value of 10.09 ± 0.36 g.m-2.hr-1. It was found that the chemical and physical modification did not only reflect on the surface of the active layer but also the porous support layer of the membrane. As a conclusion, surface modification via UV-photografting offers another route for the usage of the commercial pressuredriven membrane for FO application.